Strategi Bertahan Hidup Ibu Tunggal Mahasiswa Universitas Selama Pandemi COVID-19: Single Mothers' Survival Strategies of University Students During Covid-19 Pandemic - Priyono Tri Febrianto (Society, 2021)
The COVID-19 pandemic impacted the social and economic sectors. Family, the smallest social unit, is experiencing the impact, particularly for the woman as single-parent. Being a single parent is either a choice, decision, or condition that must be accepted due to the spouse’s passing or other condition. Single parents carried numerous burdens alone, including earning a living and raising the children. These burdens have a significant impact on single parents. This study aims to reveal single-parent families’ survival mechanisms. The research applied a qualitative method by interviewing single mothers from university students in East Java Province, Indonesia. This study used the theory of survival mechanism proposed by James Scott. The study found that instabilities generated by the COVID-19 pandemic produced enormous diminishing income. Such ordeals faced by single parents are burdensome because they initially had to support the family amid the feeble economy. Income vulnerability becomes a deep concern for single mothers. Pandemic COVID-19 caused these mothers to empower themselves and develop various survival strategies. The mothers from middle-class families live frugally and selective when they buy something they need. While mothers from lower-class families did different survival mechanisms, range from careful spending, owe some money, and open a business using their ex-husband’s savings. Furthermore, they are also working overtime, empowering their children to help with the work, diversifying jobs by opening food stalls up to have an online shop. Therefore, it can be assumed that the COVID-19 pandemic has made single parents struggle even more to fulfil their family needs.